2020
DOI: 10.1002/dvdy.159
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian hemicentin 1 is assembled into tracks in the extracellular matrix of multiple tissues

Abstract: Background: Hemicentins (HMCNs) are a family of extracellular matrix proteins first identified in Caenorhabditis elegans, with two orthologs (HMCN1 and 2) in vertebrates. In worms, HMCN is deposited at specific sites where it forms long, fine tracks that link two tissues by connecting adjacent basement membranes (BMs). By generating CRISPR/Cas9-mediated Hmcn1 and Hmcn2 knockout mice, we tested the hypothesis that HMCNs perform similar functions in mammals.Results: Hmcn1 −/− mice were viable and fertile. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Hmcn1 is mainly produced by mesenchymal cells, while Hmcn2 appears to be expressed by cells of epithelial origin. Consistent with previous reports [15], Hmcn1 -/mice generated in this study via conventional gene recombination technology, although lacking detectable Hmcn1 protein, are viable and show no obvious morphological, mechanical or locomotion phenotypes. However, transmission electron microscopy revealed ultrastructural BM alterations at the DEJ and MTJ of Hmcn1 -/mice, pointing to a thus far unknown essential role of mouse Hmcn1 for BM integrity as the prerequisite for proper tissue linkage.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hmcn1 is mainly produced by mesenchymal cells, while Hmcn2 appears to be expressed by cells of epithelial origin. Consistent with previous reports [15], Hmcn1 -/mice generated in this study via conventional gene recombination technology, although lacking detectable Hmcn1 protein, are viable and show no obvious morphological, mechanical or locomotion phenotypes. However, transmission electron microscopy revealed ultrastructural BM alterations at the DEJ and MTJ of Hmcn1 -/mice, pointing to a thus far unknown essential role of mouse Hmcn1 for BM integrity as the prerequisite for proper tissue linkage.…”
Section: Introductionsupporting
confidence: 92%
“…In mice, there are conflicting results about the importance of Hmcn1 for embryonic development. While it was initially reported that genetic ablation of Hmcn1 in mice leads to preimplantation lethality [17], a recent report showed that Hmcn1 is dispensable for murine embryogenesis [15]. To assess the functional roles of Hmcn1 and Hmcn2 during murine development, we analyzed their gene expression and their protein localization patterns at the two-cell stage (Fig.…”
Section: Hmcn1 and Hmcn2 Display Differential Distributions Throughout Developmentmentioning
confidence: 99%
See 3 more Smart Citations